2022
DOI: 10.1186/s13017-022-00407-1
|View full text |Cite
|
Sign up to set email alerts
|

Emergency surgery admissions and the COVID-19 pandemic: did the first wave really change our practice? Results of an ACOI/WSES international retrospective cohort audit on 6263 patients

Abstract: Introduction The COVID-19 pandemic is having a deep impact on emergency surgical services, with a significant reduction of patients admitted into emergency surgical units world widely. Reliable figures of this reduction have not been produced yet. Our international audit aimed at giving a precise snapshot of the absolute and relative changes of emergency surgical admissions at the outbreak of the pandemic. Materials and methods Datasets of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…Although overall patient numbers are decreasing, especially patients with bowel diseases including appendicitis and diverticulitis present in the emergency rooms with more severe, prolonged and even perforated diseases [3,8,15,16]. Besides that, Tebala et al showed in their international retrospective cohort audit correlations of hospital admissions with general patient condition and physical health [22]. These changes in patient flow into surgical emergency departments as well as the observation of higher proportion of patients with more severe and prolonged diseases might be an expression of ongoing changes in medical evaluation and decision-making processes and a kind of pandemicdriven fear reactions of patients and referring physicians against SARS-CoV-2 infection [23].…”
Section: Discussionmentioning
confidence: 99%
“…Although overall patient numbers are decreasing, especially patients with bowel diseases including appendicitis and diverticulitis present in the emergency rooms with more severe, prolonged and even perforated diseases [3,8,15,16]. Besides that, Tebala et al showed in their international retrospective cohort audit correlations of hospital admissions with general patient condition and physical health [22]. These changes in patient flow into surgical emergency departments as well as the observation of higher proportion of patients with more severe and prolonged diseases might be an expression of ongoing changes in medical evaluation and decision-making processes and a kind of pandemicdriven fear reactions of patients and referring physicians against SARS-CoV-2 infection [23].…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the course of the pandemic, many medical centers simultaneously reported a decrease in their numbers of surgeries, whether they were elective or emergent, or for cancerous or benign resections. The initial prediction made by the COVIDSurg Collaborative group was an 80% decrease in benign and a 30% decrease in malignant cancer surgeries ( Table 1 ) [ 6 7 8 9 10 11 12 13 14 15 16 17 18 19 ]. A multicenter-based report from England and Wales reported a 33.6% decrease in all types of surgeries in 2020 compared to non-pandemic periods (4,671,338 to 3,102,674) [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, elective surgery cases in the United States (US) showed a dramatic decrease (34.1% to 81.7%) in several reports, including 2 multicenter studies in the period from March to May 2020 compared to the same months in 2019 [ 9 10 11 12 ]. In addition to elective surgeries, emergent operations have also been reported to decrease by around 30% worldwide [ 13 14 15 ]. Cancer surgeries and obstetric operations have been less affected with centers reporting only a 7.8% reduction in colorectal cancer resections [ 8 ] and a 6% drop in cesarean deliveries [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…18,19 A multicentre European study had similar experiences with a shift in elderly and more frail patients and reduction in appendicitis and diverticulitis, but increase in bowel ischaemia and perianal ailments. 20 Acting within resource limitations and preparation for the wave, the LoS was significantly shorter for appendicitis and cholecystitis in the COVID-19 cohort (2.9 vs. 2.5, p=0.027). The Auckland experience similarly reported fewer operations, albeit non-significant, with a total median LoS difference of 0.5 days between the groups (1.8 vs. 1.3, p=0.031).…”
Section: Discussionmentioning
confidence: 96%